2003
DOI: 10.1007/s00418-003-0558-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the VEGF receptor-3 in osteoarthritic chondrocytes: stimulation by interleukin-1? and association with ?1-integrins

Abstract: Recent studies have demonstrated enhanced expression of vascular endothelial growth factor and vascular endothelial growth factor receptor (VEGFR)-1 and -2 in chondrocytes of rheumatoid and osteoarthritic cartilage. Since expression of VEGFR-3 ( Flt-4) in chondrocytes has not yet been investigated, we studied the distribution of VEGFR-3 in osteoarthritic cartilage samples by immunohistochemistry and immunoelectron microscopy. Furthermore, we looked for functional colocalization of VEGFR-3 with the signal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Expression of the VEGF receptors VEGFR-1, also known as Fms related tyrosine kinase 1 (FLT-1) and VEGFR-2, also known as kinase insert domain receptor (KDR) is either restricted to OA AC compared to normal AC [115], whereas other studies reported that VEGFR-1 [116] or VEGFR-2 [119] were not detectable at all in human adult AC. Moreover, in human OA AC VEGFR-3, also known as Fms-like tyrosine kinase 4 (FLT4), is expressed in the SZ cells located in cytoplasm and on cell membrane [120]. In primary OA AC monolayer cultures catabolic MMP-1 and MMP-3 mRNA expression, but not MMP-2 , MMP-9 or MMP-13 expression, can be induced by rVEGF165, whereas cultured normal AC cells exhibit no catabolic gene expression upon rVEGF165 treatment at all [115].…”
Section: Additional Growth Factor Signaling Pathways In Human Adulmentioning
confidence: 99%
“…Expression of the VEGF receptors VEGFR-1, also known as Fms related tyrosine kinase 1 (FLT-1) and VEGFR-2, also known as kinase insert domain receptor (KDR) is either restricted to OA AC compared to normal AC [115], whereas other studies reported that VEGFR-1 [116] or VEGFR-2 [119] were not detectable at all in human adult AC. Moreover, in human OA AC VEGFR-3, also known as Fms-like tyrosine kinase 4 (FLT4), is expressed in the SZ cells located in cytoplasm and on cell membrane [120]. In primary OA AC monolayer cultures catabolic MMP-1 and MMP-3 mRNA expression, but not MMP-2 , MMP-9 or MMP-13 expression, can be induced by rVEGF165, whereas cultured normal AC cells exhibit no catabolic gene expression upon rVEGF165 treatment at all [115].…”
Section: Additional Growth Factor Signaling Pathways In Human Adulmentioning
confidence: 99%
“…It is required for the development of blood as well as lymphatic vessels and is thought to have a general function in blood vascularization during early development (Lohela et al, 2003); later, its role becomes restricted mostly to the development of the lymphatic vascular system (Dayoub et al, 2003). Furthermore, expression of VEGFR-3 has been reported to be higher in human osteoarthritic chondrocytes than in persons without arthritis (Shakibaei et al, 2003).…”
Section: Vegfr-3mentioning
confidence: 99%
“…[12][13][14] The ␣ v ␤ 3 integrin associates with KDR in endothelial cells, 13 whereas the ␤ 1 subunit forms a functional complex with VEGFR-3 in chondrocytes. 15 Moreover, soluble FLT-1 secreted by endothelial cells binds to ␣ 5 ␤ 1 integrin. 16 Finally, a membrane complex containing PKC, ␤ 1 integrin, and FLT-1 has been shown to assemble in multiple myeloma cells.…”
Section: Introductionmentioning
confidence: 99%